The Portuguese consumer sentiment index toward marketing‑mix in crisis context - Fernandes,Paula Odete (2013)
The purpose of this research is to better understand the behaviour of the Portuguese consumer sentiment index toward marketing-mix in a crisis context. For this purpose we used an instrument translated and validated by the Index of Consumer Sentiment toward Marketing proposed by Gaski and Etzel (1986). This Index was used in this research since it offers a widely accepted and readily understood approach to measure citizen experiences as consumers in a society. All analysis was based on a consumer survey. The survey procedures resulted in 600 usable surveys, distributed by five regions (NUT II) in Continental Portugal. A 4% precision error and 5% of significance level were assumed. The results showed that the Portuguese consumer sentiment index toward marketing‑mix is weakly positive and could be a consequence of the present economic and financial context that the country is undergoing.